BE AND AE STARS IN PERSEUS AND CASSIOPEA - GONZALEZ, G; GONZALEZ, G (Observatorio Astrofísico de Tonantzintla, Pue, Pue, Mex, 1954)
An area of 179 square degrees lying approximately between l=90° to 103° and b=+4° to -7° has been searched with the purpose of finding early-type stars with Ha in emission and with photographic magnitudes as faint as 14.5m. During our presente work we hav
BOL OBS TONAN TACUB
Keywords: STARS, PERSEUS, CASSIOPEA; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS